Regulatory framework of the oncological medical care provision - S. N. Tishkina; V. E. Matskevich; Yu. A. Ledovskikh; E. V. Semakova; V. V. Omelyanovskiy (Фармакоэкономика)
Aim. To conduct an analytical review of the regulatory legal framework on the resources provision required in medical organizations for the provision of oncological medical care based on clinical guidelines.Materials and methods. Using Russian normative legal and regulative documents on the oncological medical care, the authors studied the normative regulation of the issues of both resources’ provision for medical organizations and resources’ demand assessment, including the need for financial support from various sources of the budgetary system of the Russian Federation. The analysis was carried out in two regulatory areas: financing and organization of the provision of medical care. The authors examined the main legislation acts relating to oncological medical care, including documents of the compulsory medical insurance, the annual decrees of the Government of the Russian Federation on the program of state guarantees of free provision of medical care to citizens for the coming year and the planned period, the decree of the Government of the Russian Federation regulating the provision of medicines and medical products, provisions on the organization of medical care by type of medical care, procedures for the provision of oncological medical care, regulatory documents on clinical guidelines and standards of medical care.Results. The content analysis of the studied materials showed that certain components of the resources’ provision, including the financial provision of oncological medical care, are regulated by various regulatory documents, and there is no methodology for assessing the resources’ demand based on clinical guidelines.Conclusion. New approaches to assessing the resources’ demand for the provision of medical care and the required financial support based on clinical guidelines need to be developed.